التكافل الاقتراني وتطبيقاته في ماليزيا من منظور الشريعة الإسلامية :‏ ‏دراسة تحليلية /‏ - توه يالا، إبراهيم (2011)
The Takaful industry at present has been one of the vital elements of national economy in many countries including Malaysia. By grace of the smart policy of the Malaysian government in the past decades, the country is facing radical development in all aspects especially in its economic sector. There has been a rapid growth in numbers of huge commercial companies, factories and other economic activities in the country which in turn has resulted in an increased demand for Takaful policy. This demand has caused a contest among Takaful operators to promote their capacity and services in order to assimilate into the markets. Despite the efforts, the gab between the capacity of Takaful operators and the rate of demand of their policy is still vast. Takaful operators therefore need to cooperate closely among themselves in order to find methods to provide a full coverage of risks. The co-Takaful is considered as one of the essential methods. It is based on four essential parties which are customers, broker companies, Takaful operator leaders and the follower companies. The researcher has carried out an investigation on the mechanism of co-Takaful and has discussed the details of it in relation to the Islamic perspective. The study concludes that co-Takaful is legitimate because it is in line with one of the Islamic corporation version which is Sharikah al-Mulk al-Ikhtiyari. However, the researcher's analysis on the relationship between parties involved in co-Takaful has shown some factors involved which are against Islamic principles. The vital roles of broker companies on co-Takaful scheme have also been highlighted. This study is generally based on a field study and findings from interviews carried out with Takaful operators in Malaysia.